2010
DOI: 10.5213/inj.2010.14.2.78
|View full text |Cite
|
Sign up to set email alerts
|

The Expression of AQP1 and eNOS in Menopausal Rat Urinary Bladder

Abstract: Purpose: Aquaporins (AQPs) have been reported to be expressed in rat and human urothelium. Nitric oxide (NO) is thought to play an important role in the bladder overactivity related to menopause. The purpose of this study was to investigate the effect of hormonal alteration on the expression of AQP1 and eNOS in menopausal rat urinary bladder. Materials and Methods: Female Sprague-Dawley rats (230-240 g, N=30) were divided into three groups: control (N=10), bilateral ovariectomy (Ovx, N=10), and bilateral ovari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…In our previous study, we reported that AQP1 was mainly expressed in the capillaries and venules of the urinary bladder and that significantly increased protein expression of AQP1 in the BOO rat urinary bladder. 13 In the current study, immunolabeling of AQP2 was expressed throughout the epithelial cell layer and detrusor smooth muscle, and AQP3 was expressed only throughout the epithelial cell layer.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…In our previous study, we reported that AQP1 was mainly expressed in the capillaries and venules of the urinary bladder and that significantly increased protein expression of AQP1 in the BOO rat urinary bladder. 13 In the current study, immunolabeling of AQP2 was expressed throughout the epithelial cell layer and detrusor smooth muscle, and AQP3 was expressed only throughout the epithelial cell layer.…”
Section: Discussionsupporting
confidence: 45%
“…12 Recently, we reported AQP1 expression in the capillaries and venules of the urinary bladder and significant incease of protein expression of AQP1 in the BOO rat urinary bladder. 13 No studies to date have investigated the expression of AQP2-3 in the urinary bladder of rats after BOO or the functional activity of these proteins in response to BOO.…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, our results showed engrafted stem cells to accelerate the rebuilding of bladder tissue by upregulating Ang1 and PDGF expression. High eNOS expression due to the stem cells also improved the restoration of damaged bladder, thereby contributing to functional improvement of the bladder [20][21][22]. We had previously observed the functional efficacy of SDF-1-overexpressing MSCs in an NB rat model [10];…”
Section: Discussionmentioning
confidence: 90%
“…Nevertheless, Giglio et al [ 48 ] have shown that 60 hours after a single intraperitoneal injection of cyclophosphamide in rats, at a time point when the innate inflammatory response is at its peak, the expression of eNOS seems to be heavily increased in the urothelium and suburothelium. Several other studies have also revealed that the expression of eNOS can vary greatly during certain disease states [ 113 , 120 ]. Apart from the urothelium, there seems to be several other sources for nitric oxide in the urinary bladder, that is, interstitial cells in the lamina propria [ 48 ] and various nerves [ 121 123 ].…”
Section: Nitric Oxidementioning
confidence: 99%